Mrs. J.B. Carmichael and the Edmonton Civic Opera Society, 1935-1971 - Berg, Wesley; Paulson, Gerry (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 1997)
Born in Indiana and trained as a singer, violinist, and conductor in Chicago and New York, Beatrice van Loon travelled to Edmonton, Alberta, in the fall of 1920 as the leader of an all-female ensemble. She married a local dentist and as Mrs. J.B. Carmichael played in the Edmonton Symphony Orchestra and conducted an orchestra at the University of Alberta until 1934. She founded the Edmonton Civic Opera Society in 1935 and worked as its artistic director until her death in 1964. For more than four decades she gave unstintingly of herself to audiences and music students in her adopted city.